The Fishbowl Strategy: An Effective Way to Improve Students’ Speaking Ability - Silitonga, Mery (Pascasarjana Universitas HKBP Nommensen, 2023)
Speaking is one of essential language skills in communication. Language teachers are expectedto bring an effective method in classroom to improve students’ speaking skills. Based on the preliminarystudy in language classroom SMAN 12 Medan, teachers had limited knowledge of creative method inteaching speaking which can be integrated to curriculum. Thus, the use of Fishbowl strategy can provideopportunity in the form of Fish and the Bowl for each student to practice speaking in the classroom whileconsidering about current curriculum. In the Fishbowl, each student can take a turn to deliver the ideas,and everyone has the equal chance to speak. This research focused on the implementation of Fishbowlstrategy to improve speaking ability of 30 students from first grade of SMAN 12 Medan. The researchmethodology was a classroom action research. At the end of implementing fishbowl, the researcher gavethe questionnaire to know students’ perception toward the use of Fishbowl strategy. Based on the researchfindings, there were 26,6% successful students at the pre-test. After conducting fishbowl, 100% ofstudents in the classroom had improvement in their speaking skill because each of them had more chanceto speak up something related to the topic given